Electrochemical Reduction of Oxygen and Nitric Oxide on Mn-Based Perovskites with Different A-Site Cations - K. Kammer Hansen (International Journal of Electrochemistry)
Four LnMnO3+δ (Ln = La, Pr, Sm, and Gd) perovskites were synthesized and characterized by powder XRD. It was shown that the perovskite lattice became more and more distorted when lowering the size of the A-site cation. The manganite-based perovskites were evaluated for the ability to electrochemically reduce oxygen and nitric oxide in the temperature range of 200 to 400°C. At the lowest temperature, the electrodes were better at reducing nitric oxide than oxygen. At higher temperatures, the activity for the reduction of oxygen and nitric oxide became similar. The activation energies for the reduction of oxygen and nitric oxide were markedly different for LaMnO3+δ and PrMnO3+δ whereas it was similar for SmMnO3+δ and GdMnO3+δ.